ISLAMIC RELIGIOUS EDUCATION LEARNING MODEL BASED ON RELIGIOUS MODERATION IN THE ERA OF DIGITAL DISRUPTION - Ahmad Izza Muttaqin; Mukniah Mukniah; Erma Fatmawati (International Conference on Humanity Education and Society (ICHES), 2023)
The purpose of this research is to describe a model of Islamic religious education based on religious moderation.The type of research used in this study is qualitative with a descriptive approach. The subjects in this study are Islamic religious education teachers, students, and principals, selected using purposive sampling. The types of data collected in this study are primary and secondary data. Data collection procedures use three techniques: observation, interviews, and documentation. Data analysis is done through data reduction, data presentation, and conclusion drawing. The model of Islamic religious education based on religious moderation applied in this study is a behavioristic learning model. The four elements of learning that must be present in the learning model are as follows: 1) Syntax: beginning with planning, implementation, and evaluation 2) The social system: learning both in and outside the classroom, even outside of school, where teachers provide ample space for students to explore their potential. Response principle: As a mediator, facilitator, and creator of a learning environment, the teacher emphasizes current religious issues regarding tolerance and religious moderation. 4) Support system: interactive multimedia learning media are still unevenly distributed in each classroom. Learning outcomes are obtained through diagnostic assessments that emphasize the learning process, and the accompanying impact is obtained through educational study activities, education camps, and homestay programs